Tantangan dan Solusi atas Komersialisasi Aplikasi Modifikasi di Indonesia Berdasarkan Undang-Undang Hak Cipta 2014 - Hasbi, Hasbi; Nadia, Nadia; Rahmatullah, Nursalam (JUSTISI, 2025)
The study aims to analyze the polemic of commercialization of modified applications in copyright enforcement through an integrative approach between legal certainty, justice and expediency. The method of research used by the author is the normative juridical method, using secondary data, in the form of primary legal materials such as Law Number 28 of 2014 concerning Copyright and its implementing regulations; secondary legal materials in the form of legal literature, journal articles, research results, legal news and legal opinion articles which are then analyzed deductively. The novelty of this research lies in the assessment of copyright law that has not reflected substantive justice in the face of infringement through the commercialization of modified applications, using the approach of Hans Kelsen's Stufenbau theory and Gustav Radbruch's Integrative theory. The results show that the polemic of copyright enforcement against modified applications is mulltidimensional. On the legal side, the unclear norms in the Copyright Law regarding application modification activities, the weak monitoring and enforcement system, and the lack of technical regulations (PP and Permenkumham) governing digital applications. On the other hand, social, cultural, and economic factors such as low legal awareness, the rampant culture of using modified applications, and the economic inability of the community also exacerbate this illegal commercialization practice. The conclusion is that copyright enforcement of modified applications is not optimal due to the gap between normative regulation and practice. Based on Gustav Radbruch's integrative theory, the solutions offered include: (1) from the aspect of justice, the government needs to change the complaint offense into an ordinary offense for application copyright infringement and issue special regulations in the form of Government Regulations or Permenkumham for the protection of digital applications, coupled with improving the integrity of law enforcement officials; (2) from the aspect of legal certainty, it is important to revise Article 52 of the Copyright Law and strengthen supervision of the distribution of modified applications by e-commerce; and (3) from the aspect of expediency, solutions include public education, the use of open source applications as an alternative, open source application development, more affordable pricing strategies, to inclusive payment systems by official developers.